PERANAN PENDIDIKAN JASMANI DALAMPEMBANGUNAN NASIONAL - M. Husni Thamrin (Jurnal Pendidikan Jasmani Indonesia, 2006)
Physical education is an integral and inseparable part with national education, which is animportant factor that will determine any national development. However, this case is oftenmissed from someone’s oversees. The ability of a society to develop its economy and toparticipate in its political existence is verily depends on educational level they have. It iscommonly believed that mankind’s improvement and development in the field of scienceknowledge, skill, behavior morality, will be obtained through education which is a way to forsubject or unit of society to grow into better. As an applied knowledge, physical educationprogram must be in accordance with national education program which is an integral andinseparable part with national development program, that is to improve quality of life ofIndonesian man as wholeness. Therefore, the goal of physical education that states adevelopment of physical fitness, metrical skill, knowledge, social, and beauties is a goalwhich is appropriate to be supported.Keywords : Role, Physical Education, National Development.